Study guides

☆☆

Q: How do you simplify 6x plus 9 plus 2x?

Write your answer...

Submit

Still have questions?

Related questions

2x + 9 = 6x + 1 9 - 1 = 6x - 2x 8 = 4x x = 2

6x - 9 + 2x + 1 = 8x -8

5x + x - 6x + 2x = 2x

9+6x = 25-2x 6x+2x = 25-9 8x = 16 x = 2

2x

There is insufficient information to answer this question. If you mean, what does x equal for: 9 + 6x = 2x ...then the answer is: 9 = 2x - 6x = -4x ...which is equal to: x = -9/4 If you mean, what does x equal for: 9 + 6x + 2x = 0 ...then the answer is: 8x = -9 ...which is equal to: x = -9/8

7x + 7 + 6x - 9 = 13x - 2

2x+9=6x-3 Therefore 4x=12 -->x=3

8x2 + 6x - 9 = 8x2 + 12x - 6x - 9 = 4x(2x + 3) - 3(2x + 3) = (2x + 3)(4x - 3)

8x2 + 6x - 9 = (2x + 3)*(4x - 3)

3+6x = 4x+9 6x-4x = 9-3 2x = 6 x = 3

2x+6x=-9 => 8x=-9=> x=-8/9

-9

8x-9 -2x plus 11 when solved mathematically is equal to 6x + 2.

If that's -9 - 6x + 9, it simplifies to -6x

4x2 - 12x + 9 = 4x2 - 6x - 6x + 9 = 2x(2x - 3) - 3(2x - 3) = (2x - 3)(2x - 3) or (2x - 3)2

0.2x + 6x - 1 = -9 6.2x = -8 x = -1.2903225806451612903225806451613

7x-9

2x + 3 = 92x = 9 - 32x = 6x = 6/2x = 3

3(x2 - 2x + 3)

3(x2 - 2x + 3)

9 - 3(2x - 4) 9 - 6x - 12 6x - 3

12x^2+10

8x^3 - 12x^2 + 6x - 9 = (8x^3 - 12x^2) + (6x - 9) = 4x^2(2x - 3) + 3(2x - 3) = (4x^2 + 3)(2x - 3)

x^2 - 2x + 3 is the other one.